Fluid–rock interactions associated with regional tectonics and basin evolution. Issue 3 (12th December 2013) - Fontana, Simone; Nader, Fadi Henri; Morad, Sadoon; Ceriani, Andrea; Al‐Aasm, Ihsan Shakir; Daniel, Jean‐Marc; Mengus, Jean‐Marie; Reijmer, John
Abstract An integrated approach consisting of fracture analysis, petrography, carbon, oxygen and strontium‐isotope analyses, as well as fluid‐inclusion micro‐thermometry, led to a better understanding of the evolution of fluid–rock interactions and diagenesis of the Upper Permian to Upper Triassic carbonates of the United Arab Emirates. The deposited carbonates were first marked by extensive early dolomitization. During progressive burial, the carbonates were affected by dolomite recrystallization as well as precipitation of vug and fracture‐filling dolomite, quartz and calcite cements. After considerable burial during the Middle Cretaceous, sub‐vertical north–south oriented fractures (F1) were cemented by dolomite derived from mesosaline to hypersaline fluids. Upon the Late Cretaceous maximum burial and ophiolite obduction, sub‐vertical east–west fractures (F2) were cemented by dolomite (Dc2) and saddle dolomite (Ds) derived from hot, highly saline fluids. Then, minor quartz cement has precipitated in fractures from hydrothermal brines. Fluid‐inclusion analyses of the various diagenetic phases imply the involvement of increasingly hot (200°C) saline brines (20 to 23% NaCl eq.). Through one‐dimensional burial history numerical modelling, the maximum temperatures reached by the studied rocks are estimated to be in the range of 160 to 200°C. Tectonically‐driven flux of hot fluids and associated diagenetic products are interpreted to have initiated during the Late Cretaceous maximum burial and lasted until the Oligocene–Miocene compressional tectonics and related uplift. The circulation of such hydrothermal brines led to partial dissolution of dolomites (Dc2 and Ds) and to precipitation of hydrothermal calcite C1 in new (mainly oriented north–south; F3) and pre‐existing, reactivated fractures. The integration of the obtained data confirms that the diagenetic evolution was controlled primarily by the interplay of the burial thermal evolution of the basin and the regional tectonic history. Hence, this contribution highlights the impacts of regional tectonics and basin history on diagenetic processes, which may subsequently affect reservoir properties.